Acute Aortic Dissection Diagnosed after Embalming: Macroscopic and Microscopic Findings1. Issue 5 (31st March 2014) - Savall, Frédéric; Dedouit, Fabrice; Piercecchi‐Marti, Marie‐Dominique; Leonetti, Georges; Rougé, Daniel; Telmon, Norbert
Abstract A 58‐year‐old man died suddenly in Madagascar and poisoning was suspected. The body was embalmed after death and the general state of preservation was good. We found a major aortic dissection with a large false lumen from the aortic root to the common iliac arteries and a hemopericardium with formalinized blood clot. The intimal tear was on the ascending aorta, and an intramural hemorrhage was noted at the right coronary artery, attesting to a retrograde dissection. Microscopic studies confirmed aortic dissection with extensive intramural hemorrhage and also confirmed the retrograde dissection to the right coronary artery with a reduction of 90% of the true lumen. Classically, aortic dissection occurs in individuals with hypertension and individuals with genetic disorders of collagen formation. The diagnosis is often first established at the postmortem examination. Aortic dissection is therefore dealt with largely in necropsy studies. The usual cause of death is rupture into the pericardial sac. One case of bloodless dissection has been reported but the sudden death was explained by acute myocardial ischemia secondary to dissection of the left coronary artery. In our case, we found major hemopericardium and also intramural hemorrhage at the right coronary artery. We were able to make the diagnosis of aortic dissection and exclude the suspicion of homicide 15 days after death and after embalming.